Nanomechanical state amplifier based on optical inverted pendulum - Duchaň, Martin; Šiler, Martin; Jákl, Petr; Brzobohatý, Oto; Rakhubovsky, Andrey; Filip, Radim; Zemánek, Pavel (Communications Physics, 2025)
Keywords: LF; MF

PT-like phase transition and limit cycle oscillations in non-reciprocally coupled optomechanical oscillators levitated in vacuum - Liška, Vojtěch; Zemánková, Tereza; Jákl, Petr; Šiler, Martin; Simpson, Stephen H.; Zemánek, Pavel; Brzobohatý, Oto (Nat. Phys., 2024)
Nanoparticles levitated in an optical trap provide a versatile platform to study mechanical oscillators in a controlled environment with tuneable parameters. Recently, it has become possible to couple two of these optomechanical oscillators. Here we demonstrate the collective non-Hermitian dynamics of such a pair of non-conservatively coupled oscillators. We take advantage of the tunability of the optical interactions between the particles in our system and set the optical interaction between the particles to be purely non-reciprocal. By continuously varying the relative power of the trapping beams, we take the system through a transition similar to a parity–time phase transition. A Hopf bifurcation at a critical point results in the formation of collective limit cycle oscillations, resembling those observed in phonon lasers. These coupled levitated oscillators provide a platform for exceptional point optomechanical sensing and can be extended to multi-particle systems, paving the way for the development of topological optomechanical media.
Keywords: LF; MF

110 mu m thin endo-microscope for deep-brain in vivo observations of neuronal connectivity, activity and blood flow dynamics - Stibůrek, Miroslav; Ondráčková, Petra; Tuckova, Tereza; Turtaev, Sergey; Šiler, Martin; Pikálek, Tomáš; Jákl, Petr; Gomes, Andre; Krejci, Jana; Kolbabkova, Petra; Uhlirova, Hana; Cizmar, Tomas (NATURE COMMUNICATIONS, 2023)
Keywords: KF; MF

Synchronization of spin-driven limit cycle oscillators optically levitated in vacuum - Brzobohatý, Oto; Duchaň, Martin; Jákl, Petr; Ježek, Jan; Šiler, Martin; Zemánek, Pavel; Simpson, Stephen H. (Nature Communications, 2023)
Keywords: LF; MF

Endoscopic Imaging Using a Multimode Optical Fibre Calibrated with Multiple Internal References - Jákl, Petr; Šiler, Martin; Ježek, Jan; Cifuentes, Angel; Trägårdh, Johanna; Zemánek, Pavel; Cizmar, Tomas (Photonics, 2022)
Keywords: BF; KF; MF

Spin to orbital light momentum conversion visualized by particle trajectory - Alejandro V. Arzola; Lukáš Chvátal; P Jákl; P. Zemánek (Sci. Rep., 2019)
Keywords: LF; MF

Diffusing up the Hill: Dynamics and Equipartition in Highly Unstable Systems - M Šiler; Ornigotti, L.; Oto Brzobohatý; P Jákl; Artem Ryabov; Holubec, V.; P. Zemánek; Radim Filip (Phys. Rev. Lett., 2018)
Keywords: LF; MF

Transverse spin forces and non-equilibrium particle dynamics in a circularly polarized vacuum optical trap - Vojtech Svak; Oto Brzobohatý; M Šiler; P Jákl; J. Kaňka; P. Zemánek; S. H. Simpson (Nature Commun., 2018)
Keywords: LF; MF

Omnidirectional Transport in Fully Reconfigurable Two Dimensional Optical Ratchets - Alejandro V. Arzola; Villasante-Barahona, Mario; Karen Volke-Sepúlveda; P Jákl; P. Zemánek (Phys. Rev. Lett., 2017)
Keywords: LF; MF

Thermally induced micro-motion by inflection in optical potential - M Šiler; P Jákl; Oto Brzobohatý; Artem Ryabov; Radim Filip; P. Zemánek (Sci. Rep., 2017)
Keywords: LF; MF

Direct measurement of the temperature profile close to an optically trapped absorbing particle - M Šiler; J Ježek; P Jákl; Z. Pilát; P. Zemánek (Opt. Lett., 2016)
Keywords: MF

Holographic Raman tweezers controlled by Multimodal Natural User Interface - Z. Tomori; P. Keša; M. Nikorovič; J. Kaňka; P Jákl; M. Šerý; Silva Bernatová; E. Valušová; M. Antalík; P. Zemánek (J. Opt., 2016)
Keywords: MF

Noise-to-signal transition of a Brownian particle in the cubic potential: II. optical trapping geometry - P. Zemánek; M Šiler; Oto Brzobohatý; P Jákl; Radim Filip (Journal of Optics, 2016)
Keywords: MF

Complex rotational dynamics of multiple spheroidal particles in a circularly polarized, dual beam trap - Oto Brzobohatý; Alejandro V. Arzola; M Šiler; Lukáš Chvátal; P Jákl; S. H. Simpson; P. Zemánek (Opt. Express, 2015)
Keywords: MF

Optical sorting of nonspherical and living microobjects in moving interference structures - P Jákl; Alejandro V. Arzola; M Šiler; Lukáš Chvátal; Karen Volke-Sepúlveda; P. Zemánek (Opt. Express, 2014)
Keywords: MF

Rotation, oscillation and hydrodynamic synchronization of optically trapped oblate spheroidal microparticles - Alejandro V. Arzola; P Jákl; Lukáš Chvátal; P. Zemánek (Opt. Express, 2014)
Keywords: MF

Following the mechanisms of bacteriostatic versus bacericidal action using Raman spectroscopy - Silva Bernatová; O. Samek; Z. Pilát; M. Šerý; J Ježek; P Jákl; M Šiler; V. Krzyžánek; P. Zemánek; V. Holá; M. Dvořáčková; F. Růžička (Molecules, 2013)
Keywords: MF

Holographic Raman tweezers controlled by hand gestures and voice commands - Z. Tomori; M. Antalík; P. Keša; J. Kaňka; P Jákl; M. Šerý; Silva Bernatová; P. Zemánek (Optics and Photonics Journal, 2013)
Keywords: MF

Optical manipulation of aerosol droplets using a holographic dual and single beam trap - Oto Brzobohatý; M Šiler; J Ježek; P Jákl; P. Zemánek (Opt. Lett., 2013)
Keywords: MF

Optical forces induced behavior of a particle in a non-diffracting vortex beam - M Šiler; P Jákl; Oto Brzobohatý; P. Zemánek (Opt. Express, 2012)
Keywords: MF

Static optical sorting in a laser interference field - P Jákl; Tomáš Čižmár; M. Šerý; P. Zemánek (Appl. Phys. Lett., 2008)
Keywords: MF

Axial optical trap stiffness influenced by retro-reflected beam - P Jákl; M. Šerý; J Ježek; M. Liška; P. Zemánek (J. Opt. A: Pure Appl. Opt., 2007)
Keywords: MF

Opto-fluidic micromanipulation system based on integrated polymer waveguides - P Jákl; M. Šerý; J Ježek; P. Zemánek; Ormos, P.; Valkai, S.; Kelemen, L. (J. Optoel Adv. Mater., 2007)
Keywords: MF

Behaviour of an optically trapped probe approaching a dielectric interface - P Jákl; M. Šerý; J Ježek; A. Jonáš; M. Liška; P. Zemánek (J Mod. Optics, 2003)
Keywords: MF

Theoretical comparison of optical traps created by standing wave and single beam - P. Zemánek; A. Jonáš; P Jákl; M. Šerý; J Ježek; M. Liška (Opt. Commun., 2003)
Keywords: MF